Inventorization and Consensus Analysis of Ethnoveterinary Medicinal Knowledge Among the Local People in Eastern India: Perception, Cultural Significance, and Resilience - Mandal, Suman Kalyan; Rahaman, Chowdhury Habibur (Frontiers in Pharmacology, 2022)
Background: Livestock is the main backbone of the rural economy of an agriculture-based country like India. To mitigate the economic loss due to livestocks’ poor performance and illness, folk phytotherapy for livestock healthcare is still actively practiced in India. Literature survey revealed that the laterite region of eastern India, characterized by its cultural, ethnic, and biological diversity as well as topographical uniqueness, lacks comprehensive information on ethnoveterinary medicinal knowledge. The objective of the present study includes documentation of traditional knowledge of Ethnoveterinary medicine (EVM) from the northern laterite region in eastern India. Methods: Ethnoveterinary medicinal data were collected using a semi-structured questionnaire, free listing, and focus group discussions. Factor for Informants’ Consensus (Fic), Fidelity Level (FL), and Cultural Value index (CV) have been employed for quantitative analyses. Jaccard index (JI) was used to check the knowledge similarity. Result: Altogether, 1234 citations were made by 132 participants. Recorded 232 ethnomedicinal species are used for preparing 307 remedies to treat 79 health disorders of livestock. Recorded species are distributed in 92 families, and Fabaceae is identified as most medicinally diversified. Uses of 24 Angiospermic taxa, one Pteridophyte, and two Fungal species were found exclusively new to the existing inventory of Indian traditional ethnoveterinary medicine. In 20 disease categories, informant consensus (Fic) value ranges from 0.4 to 0.83. According to the FL value and use-mention factor, 23 EVM plants have been identified as the most important species in the respective disease categories. Value of CV index highlighted nine species as culturally most significant (CV ≥ 0.0025 and frequency of citation ≥ 20) in the laterite region of eastern India. Conclusion: Large extent of recorded data is quite worthy for the Indian folk veterinary medicinal repository. A handful of new data reported here and statistically justified culturally most significant species will provide the golden opportunity for bioprospecting research.